The Secrets of the Forest: Tourist Images about Puerto Patriada (Patagonia, Argentina) - Crespo, Carolina (2022)
Fil: Crespo, Carolina. Universidad de Buenos Aires. Instituto Nacional de Antropología y Pensamiento Latinoamericano. Buenos Aires; Argentina.